2005
DOI: 10.1308/003588405x51137
|View full text |Cite
|
Sign up to set email alerts
|

Routine magnetic resonance cholangiopancreatography and intra-operative cholangiogram in the evaluation of common bile duct stones

Abstract: Magnetic resonance cholangiopancreatography (MRCP) is increasingly replacing diagnostic endoscopic retrograde cholangiopancreatography (ERCP) in the initial assessment of patients suspected biliary obstruction, 1 with ERCP being reserved for the removal of confirmed stones in choledocholithiasis.2 However, the optimum method of investigating suspected common bile duct stones is still under debate. MRCP has been shown to be sensitive and specific in the evaluation of choledocholithiasis when compared to ERCP. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…Dalton SJ et al compared MRCP with ERCP and their outcome have confirmed that MRCP has an accuracy of about 95%; and especially negative predictive value reaches 100%. 19 Topal B et al compared MRCP findings with that of ERCP have concluded that dependence upon MRCP might have cut down the requirement for ERCP and sphincterotomy by up to 75%. 20 For these reasons, MRCP has been included in the investigation of pancreatobiliary pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Dalton SJ et al compared MRCP with ERCP and their outcome have confirmed that MRCP has an accuracy of about 95%; and especially negative predictive value reaches 100%. 19 Topal B et al compared MRCP findings with that of ERCP have concluded that dependence upon MRCP might have cut down the requirement for ERCP and sphincterotomy by up to 75%. 20 For these reasons, MRCP has been included in the investigation of pancreatobiliary pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Les performances diagnostiques des examens de deuxième intention sont résumées dans le tableau I [45][46][47]. Ces techniques sont choisies en fonction des disponibilités locales et du choix stratégique de prise en charge.…”
Section: Imagerieunclassified
“…Performances des examens de deuxième intention pour le diagnostic de lithiase de la voie biliaire principale[45][46][47] VPP = 99 % quand tous les facteurs sont présents…”
unclassified
“…However, ERCP is associated with significant morbidity and mortality 15 . With the development of accurate preoperative non-invasive CBD imaging based on magnetic resonance cholangiopancreatography, further complex preoperative algorithms were instituted 16 . Today, the laparoscopic management of choledocholithiasis is increasingly reported with the emergence of an argument to return to one-stage surgical management of choledocholithiasis 17 ; this has not been widely accepted by general surgeons 5 .…”
Section: Introductionmentioning
confidence: 99%